2019
DOI: 10.1016/j.enconman.2019.111997
|View full text |Cite
|
Sign up to set email alerts
|

Exergy and economic assessments of solar organic Rankine cycle system with linear V-Shape cavity

Abstract: This is a repository copy of Exergy and economic assessments of solar organic Rankine cycle system with linear V-Shape cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…The ratio of the collecting area to the storage tank is found to be 11.43 m 2 /m 3 in the overall optimum case. This value is different compared to another previous study of the same research team where this ratio was found 80 m 2 /m 3 [15]. There are many reasons for this difference in the found values.…”
contrasting
confidence: 88%
See 2 more Smart Citations
“…The ratio of the collecting area to the storage tank is found to be 11.43 m 2 /m 3 in the overall optimum case. This value is different compared to another previous study of the same research team where this ratio was found 80 m 2 /m 3 [15]. There are many reasons for this difference in the found values.…”
contrasting
confidence: 88%
“…The optimum ratio of the collecting area to storage tank volume was found at 80 m 2 /m 3 , and, for this case, the system efficiency is 13.46% and the payback period is at 9 years. Askari-Asli Ardeh et al [15] examined a PTC with a V-shape cavity coupled to an ORC. They found that this unit is able to lead to a payback period lower than 9 years and to a system efficiency of about 25% in optimal design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that increasing the efficiency of the system is viable with increasing the incoming solar radiation and the inlet temperature of the fluid as well as the decrease of fluid flow rate. They calculated the lowest levelized cost of electricity (LCOE), the lowest payback period, and the number of years for the optimum condition of the developed solar‐organic Rankine cycle system 18 …”
Section: Introductionmentioning
confidence: 99%
“…They calculated the lowest levelized cost of electricity (LCOE), the lowest payback period, and the number of years for the optimum condition of the developed solar-organic Rankine cycle system. 18 Based on the above-reviewed research, it seems a more comprehensive study of combined Rankine organic cycles with solar PV systems could be valuable to designers of utility scale solar systems. In the present research, energy, and economic analyses of three power generation plants, including a PV, a CPV, and an integrated CPV/T with a Rankine organic cycle plant were carried out in different parts of Iran.…”
mentioning
confidence: 99%